Laparoscopic lavage versus resection in perforated diverticulitis with purulent peritonitis: a meta-analysis of randomized controlled trials. Issue 1 (December 2016) - Ceresoli, Marco; Coccolini, Federico; Montori, Giulia; Catena, Fausto; Sartelli, Massimo; Ansaloni, Luca
Abstract Objective Purulent peritonitis from acute left colon diverticulitis is a relatively common presentation of diverticular disease; historically the treatment was the Hartmann procedure. Laparoscopic peritoneal lavage has been proposed as a lesser invasive treatment option with great interest and debate among surgeons and with contrasting results. The aim of this meta-analysis was to compare the results of sigmoid resection with laparoscopic lavage. Methods A systematic review was performed to select randomized controlled trials comparing laparoscopic lavage versus resection in Hinchey III diverticulitis. Studies' selection, data extraction and risk of bias assessment were done by two independent authors; results were shown as OR with 95 % C.I. Results Three RCT were selected for the meta-analysis including 315 patents. Laparoscopic lavage was associated with significantly more reoperations (OR 3.75, p = 0.006) and more intra-abdominal abscesses (OR 3.50, p = 0.0003) with no differences in mortality (OR 0.93, p = 0.92). At 12 months follow up laparoscopic lavage was associated with lesser reoperations (OR 0.32, p = 0.0004); there were no differences in term of stoma presence (OR 0.44p = 0.27) and mortality (OR 0.74p = 0.51). Conclusions The present meta-analysis shows that in acute perforated diverticulitis with purulent peritonitis laparoscopic lavage is comparable to sigmoid resection in term of mortality but it is associated with a significantly higher rate of reoperations and a higher rate of intra-abdominal abscess. No differences in term of mortality were demonstrated at follow-up. Further studies are needed to better define the safety and appropriateness of this treatment.